18F‐FDG PET/CT vs. human papillomavirus, p16 and Epstein–Barr virus detection in cervical metastatic lymph nodes for identifying primary tumors. Issue 6 (15th March 2017) - Cheol Park, Gi; Roh, Jong‐Lyel; Cho, Kyung‐Ja; Seung Kim, Jae; Hyeon Jin, Mi; Choi, Seung‐Ho; Yuhl Nam, Soon; Yoon Kim, Sang
Abstract : Squamous cell carcinoma of unknown primary of the head and neck (SCCUP) is a heterogeneous disease entity that requires careful examination to locate the occult primary. We examined the diagnostic value of expression of biomarkers, such as human papillomavirus (HPV), p16 and Epstein–Barr virus (EBV), in metastatic lymph nodes vs . 18 F‐fluorodeoxyglucose ( 18 F‐FDG) positron emission tomography/computed tomography (PET/CT). We prospectively enrolled 54 consecutive SCCUP patients who received HPV, p16 and EBV analyses of lymph node fine‐needle aspirates and 18 F‐FDG PET/CT scans and subsequently underwent examinations and biopsies under general anesthesia to detect primary tumors. The diagnostic performance of the biomarkers and 18 F‐FDG PET/CT were compared by using receiver operating characteristics (ROC) curve analyses with histopathological results for identification of primary tumors. Primary tumors were identified in 28 (51.9%) of 54 patients: the palatine tonsil in 24, base of the tongue in 1, nasopharynx in 2, and hypopharynx in 1. The sensitivity of p16 (85.7%) and accuracy of HPV (85.2%) were higher than those (42.9% and 68.5%) of 18 F‐FDG PET/CT ( p < 0.05). The area under the ROC curve of HPV was higher than that of 18 F‐FDG PET/CT (0.857 vs . 0.666, p = 0.007). The disease‐free survival rates were higher in the patients with primary tumor detection or p16 nodal immunopositivity than in the other patients ( p < 0.05). The results showed that HPV and p16 detection in metastatic lymph nodes can help locate hidden primary tumors, guide definitive treatment and predict patient survival. Abstract : What's new? Diagnosis of squamous cell carcinoma of unknown primary of the head and neck (SCCUP) is notoriously difficult, and primary tumor sites remain unknown in some patients. To improve SCCUP diagnosis, the authors of our study explored the possibility of using human papillomavirus (HPV) and related biomarkers. Compared to 18 F‐fluorodeoxyglucose ( 18 F‐FDG) positron emission tomography/computed tomography, lymph node HPV and p16 positivity exhibited increased sensitivity and specificity for primary SCCUP identification. The findings suggest that the examination of nodal biomarkers is a useful in diagnostic approach for SCCUP, with the potential to guide site‐specific treatment and predict treatment outcomes.